Performance and politics in Tanzania the nation on stage - Edmondson, Laura (Bloomington Indiana University Press, 2007)
In Performance and Politics in Tanzania, Laura Edmondson examines how politics, social values, and gender are expressed on stage. Now a disappearing tradition, Tanzanian popular theatre integrates comic sketches, acrobatics, melodrama, song, and dance to produce lively commentaries on what it means to be Tanzanian. These dynamic shows invite improvisation and spontaneous and raucous audience participation as they explore popular sentiments. Edmondson asserts that these performances overturn the boundary between official and popular art and offer a new way of thinking about African popular culture. She discusses how the blurring of state agendas and local desires presents a charged environment for the exploration of Tanzanian political and social realities: What is the meaning of democracy and who gets to define it? Who is in power, and how is power exposed or concealed? What is the role of tradition in a postsocialist state? How will the future of the nation be negotiated? This engaging book provides important insight into the complexity of popular forms of expression during a time of political and social change in East Africa.
Includes bibliographical references (p. [143]-168) and index.
Keywords: Performing arts--Political aspects--Tanzania.